2022
DOI: 10.1017/s1759078722000149
|View full text |Cite
|
Sign up to set email alerts
|

SIW cavity-backed dual inverted L slot antenna array for Ku band applications

Abstract: A novel concept of SIW cavity-backed dual inverted edge curved L slots antenna array with the defective ground plane is proposed in this paper. A linearly placed six-element inverted dual L slots array antenna is designed separated by a distance of 0.55λ g to achieve high gain. Each pair of slots is separated by a column of the vias to form sub-cavities and those are fed individually. Defective ground structure (DGS) is introduced at the ground plane to manage the propagation of wave to the last s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A concave L‐shaped flap‐oriented coplanar antenna for multi‐band applications is proposed by Bag et al 27 Substrate integrated waveguide (SIW) based hexagonal‐shaped antenna is reported by Liu et al 28 A high‐gain spiral‐shaped printed antenna has been proposed for direct broadcast satellite applications by Kola et al 29 An open‐ended SIW‐based U‐shaped antenna for Ku‐band applications is proposed by Ameen et al 30 The wireless application based high‐gain printed antenna is reported by Kola et al 31 Wang et al 32 claimed that the developed U‐slot inside the radiator helps to enhance the parametric results in terms of directivity and return‐loss bandwidth. A four‐element antenna array could improve parametric results as reported in several literature 33–44 …”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…A concave L‐shaped flap‐oriented coplanar antenna for multi‐band applications is proposed by Bag et al 27 Substrate integrated waveguide (SIW) based hexagonal‐shaped antenna is reported by Liu et al 28 A high‐gain spiral‐shaped printed antenna has been proposed for direct broadcast satellite applications by Kola et al 29 An open‐ended SIW‐based U‐shaped antenna for Ku‐band applications is proposed by Ameen et al 30 The wireless application based high‐gain printed antenna is reported by Kola et al 31 Wang et al 32 claimed that the developed U‐slot inside the radiator helps to enhance the parametric results in terms of directivity and return‐loss bandwidth. A four‐element antenna array could improve parametric results as reported in several literature 33–44 …”
Section: Introductionmentioning
confidence: 75%
“…A four-element antenna array could improve parametric results as reported in several literature. [33][34][35][36][37][38][39][40][41][42][43][44] A printed antenna 45 and its array with a natureinspired design that gives enormous gain and shallow x-pol. levels throughout its main beam's path are described in this paper by the authors.…”
Section: Introductionmentioning
confidence: 99%
“…Half-mode SIW (HMSIW) and Folded half-mode SIW (FHMSIW) designs have significantly reduced the physical footprint of various RF components while maintaining excellent performance. They are widely used in power dividers, filters, and antennas, utilizing complex techniques like quartermode, half-mode, and folding SIW cavities [5,[6][7][8][9][10][11][12][13]. Further, it is especially significant to trace the progress of fixed/tunable filters.…”
Section: Introductionmentioning
confidence: 99%